2008
DOI: 10.1177/000348940811701204
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Esophagoscopy: White-Light versus Narrowband Imaging

Abstract: Narrowband imaging may be a useful adjunct in increasing the diagnostic sensitivity of TNE in the hands of the otolaryngologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Inspection of the mucosa is performed by pulling the endoscope slowly upward in a circumferential manner. For inspection of the esophagus, air is blown through the working channel to open the esophagus . The gastrointestinal junction is difficult to inspect and requires more time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspection of the mucosa is performed by pulling the endoscope slowly upward in a circumferential manner. For inspection of the esophagus, air is blown through the working channel to open the esophagus . The gastrointestinal junction is difficult to inspect and requires more time.…”
Section: Resultsmentioning
confidence: 99%
“…For inspection of the esophagus, air is blown through the working channel to open the esophagus. 4,6,7,[15][16][17][18]20,21,24,25,29,[31][32][33][37][38][39]42,43,[47][48][49][50]52,57,[63][64][65][66] The gastrointestinal junction is difficult to inspect and requires more time. The caudal portion of the gastrointestinal junction can be visualized by passing the endoscope in the gastric cardia and by performing a retroflexion of the tip of the endoscope up to 210 8, although not all endoscopes possess this feature.…”
mentioning
confidence: 99%
“…The total number of the patients assessed in the studies was 502 (range per study 11–173), who had 3988 (35–1190) lesions assessed with NBI and compared with histopathology. Seven of the excluded studies were interobesever studies with no data available on true negatives or false positives for calculating sensitivity and specificitity . Three other excluded studies were not in accordance with the inclusive criteria .…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the excluded studies were interobesever studies with no data available on true negatives or false positives for calculating sensitivity and specificitity. [20][21][22][23][24][25][26] Three other excluded studies were not in accordance with the inclusive criteria. [27][28][29] Five studies gave details of HGD or SIM characterization on a per-patient analysis, 9,[15][16][17] and five studies revealed data for per-lesion basis.…”
Section: Description Of the Study Characteristicsmentioning
confidence: 99%
“…A recent report of sidestream dark-field video microscopy identified alterations in the oral mucosal microvasculature circulation that could represent an important mechanism of early tissue injury35. Narrow band imaging is an optical filter technology that can differentiate between deep and shallow blood vessels, which could provide additional insight into mucosal-based change secondary to cancer therapy36, 37.…”
Section: Imaging Technologymentioning
confidence: 99%